2010
DOI: 10.1016/j.annemergmed.2010.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Strategies for Diagnosing Pulmonary Embolism Among Emergency Department Patients Presenting With Undifferentiated Symptoms

Abstract: Objective Symptoms associated with pulmonary embolism (PE) can be nonspecific and similar to many competing diagnoses, leading to excessive costly testing and treatment as well as missed diagnoses. Objective studies are essential for diagnosis. This study evaluates the cost-effectiveness of different diagnostic strategies in an Emergency Department (ED) for patients presenting with undifferentiated symptoms suggestive of PE. Methods Using a probabilistic decision model, we evaluated the incremental costs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 146 publications
0
24
0
1
Order By: Relevance
“…The new cutoff minimize radiation exposure by eliminating unnecessary scans, thus the slightly reduced sensitivity could be neglected. Similarly, other reports identified that base lines of D-dimer were higher in the elderly (Smith-Bindman et al, 2009;Duriseti et al, 2010;Kabrhel et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…The new cutoff minimize radiation exposure by eliminating unnecessary scans, thus the slightly reduced sensitivity could be neglected. Similarly, other reports identified that base lines of D-dimer were higher in the elderly (Smith-Bindman et al, 2009;Duriseti et al, 2010;Kabrhel et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…5,29,[40][41][42] Two studies were excluded because they were simply cost analyses and as such did not consider outcomes associated with each test. 34,35 All studies incorporated clinical probability assessment. 34,35 All studies incorporated clinical probability assessment.…”
Section: Resultsmentioning
confidence: 99%
“…20,[33][34][35][36] The direct costs reported in the study by Ward et al 33 were extracted from Medicare data, and professional fees were taken from the National Physician Fee Schedule. 20,[33][34][35][36] The direct costs reported in the study by Ward et al 33 were extracted from Medicare data, and professional fees were taken from the National Physician Fee Schedule.…”
Section: Costsmentioning
confidence: 99%
“…The relevance of obesity with regards to PE was widely reported by some European and American published series (Heit et al, 2010;Duriseti et al, 2010;Goldhaber et al, 1983;Goldhaber, 2010). For Goldhaber et al (1983Goldhaber et al ( , 2010, obesity is an important long-term factor for significant PE at autopsy, and maintaining lower weight might decrease the risk of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%